Intorno a Boccaccio / Boccaccio e dintorni 2015 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 9 settembre 2015) - Zamponi, Stefano (Studi e saggi, 2016)
The work Intorno a Boccaccio/Boccaccio e dintorni 2015 stems from the international seminar that was held in Certaldo on the 9th September 2015, and is the second edition of an initiative which the ENGB National Association has now made an annual appointment. The purpose of these seminars, aimed primarily at young scholars, is to collect and develop the research prospects emerged in occasion of the centenary celebrations in 2013 and to offer a place for a new and contemporary discussion. The topics covered during the seminar, mainly focused on the Latin and vernacular work of Boccaccio, address (with specific attention to the Decameron) aspects of tradition and textual criticism, history of the language, literary criticism and history of the miniature.